Glucosamine Inhibits the Proliferation of Hepatocellular Carcinoma Cells by Eliciting Apoptosis, Autophagy, and the Anti-Warburg Effect - Misako Samizu; Kaoruko Iida (Scientifica)
Although glucosamine (GlcN) exhibits antitumor effects, its mechanism of action remains controversial. Additionally, its impact on hepatocellular carcinoma (HCC) is not well understood. This study aimed to investigate the antitumor effects of GlcN and its underlying mechanism in a mouse HCC cell line, Hepa1-6. GlcN treatment significantly inhibited Hepa1-6 cell proliferation. Gene expression analysis revealed that GlcN upregulated Chop and Bax while downregulating Bcl2, indicating the involvement of endoplasmic reticulum (ER) stress-induced apoptosis in the antiproliferative effects of GlcN. GlcN also increased the expression of FoxO1 and FoxO3, known tumor suppressors in various cancers. Furthermore, GlcN treatment elevated the levels of LC3II (an autophagy marker) and AMP-activated protein kinase activity, suggesting intracellular energy shortage. Indeed, GlcN treatment significantly suppressed glycolytic flux, lactate, and ATP production. Supplementing GlcN treatment with a high glucose concentration (20 mM) significantly attenuated its effect. We postulate that GlcN inhibits Hepa1-6 cell growth by inducing ER stress-induced apoptosis and autophagy and by inhibiting aerobic glycolysis (the Warburg effect), a key hallmark of cancer metabolism. Given that glucose transporter 2 (GLUT2), which is abundantly expressed in hepatocytes, has a high affinity for GlcN, these effects may result from GlcN competing with glucose for hepatocyte uptake by GLUT2. Our novel findings have potential implications for HCC treatment.